Orlistat accelerates gastric emptying and attenuates GIP release in healthy subjects - HAKLAR, GONCAGÜL; DEDE, FUAT; BEKİROĞLU, GÜLNAZ NURAL; TUROĞLU, HALİL TURGUT; ÖNEŞ, TUNÇ (AMER PHYSIOLOGICAL SOC, 2009)
Enc, FY, Ones,T, Akin HL, Dede F, Turoglu HT, Ulfer G, Bekiroglu N, Haklar G, Rehfeld JF, Holst JJ, Ulusoy NB, Imeryuz N. Orlistat accelerates gastric emptying and attenuates GIP release in healthy subjects. Am J Physiol Gastrointest Liver Physiol 296: G482-G489, 2009. First published December 24, 2008; doi:10.1152/ajpgi.90209.2008.-Orlistat, an inhibitor of digestive lipases, is widely used for the treatment of obesity. Previous reports on the effect of orally ingested orlistat together with a meal on gastric emptying and secretion of gut peptides that modulate postprandial responses are controversial. We investigated the effect of ingested orlistat on gastric emptying and plasma responses of gut peptides in response to a solid mixed meal with a moderate energy load. In healthy subjects, gastric emptying was determined using scintigraphy and studies were performed without and with 120 mg of orlistat in pellet form in random order. Orlistat shortened t lag and t half and decreased the area under the gastric emptying curve. Orlistat significantly attenuated the secretion of glucose-dependent insulinotropic polypeptide (GIP) but did not alter the plasma responses of cholecystokinin (CCK), glucagon-like peptide-1 (GLP-1), pancreatic polypeptide (PP), and insulin. There was no peptide YY (PYY) response. Area under the curve of gastric emptying was positively correlated with integrated secretion of GIP (r = 0.786) in orlistat and was negatively correlated with integrated plasma response of GLP-1 (r = -0.75) in control experiments, implying that inhibition of fat absorption modifies determinants of gastric emptying of a meal. Orlistat administered similar to its use in obesity treatment accelerates gastric emptying of a solid mixed meal with a moderate energy load and profoundly attenuates release of GIP without appreciably altering plasma responses of CCK, GLP-1, and PP. Since GIP is being implemented in the development of obesity, its role in weight control attained by orlistat awaits further investigation.
Keywords: glucose-dependent insulinotropic polypeptide; glucagon like peptide-1; peptide YY; pancreatic polypeptide; cholecyctokinin; obesity; brain-gut axis; GLUCAGON-LIKE PEPTIDE-1; DEPENDENT INSULINOTROPIC POLYPEPTIDE; TYPE-2 DIABETES-MELLITUS; FREE FATTY-ACIDS; PANCREATIC-POLYPEPTIDE; LIPASE INHIBITION; GALLBLADDER CONTRACTION; RECEPTOR BLOCKADE; GUT HORMONES; FOOD-INTAKE